Volksrepublik China: Popularisierung von Archäologie und Kulturerbe - Wertmann, Patrick (e-Forschungsberichte des DAI, 2023)
In recent years, financial power, political drive and educational objectives are strongly reflected in China in the construction of new museums and the popularization of archaeological discoveries. Given the trading networks that extended over Asia and further beyond to Europe and Africa during the Han (206 BC – 220 AD) and Tang (618–907) dynasties, the cultural heritage from these periods is now widely celebrated and revived. Patrick Wertmann from the Beijing branch office investigates contents and goals of museums and popular scientific magazines as well as the use of new media aiming at disseminating the knowledge about cultural heritage in China.